2014
DOI: 10.1161/strokeaha.113.004251
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel Plus Aspirin Versus Warfarin in Patients With Stroke and Aortic Arch Plaques

Abstract: Retrospective, unblinded, nonrandomized comparisons between these 2 strategies have been inconclusive 13 and no randomized evaluation of these strategies has been conducted.14 We hypothesized that the combination of aspirin plus clopidogrel was 25% superior to dose-adjusted warfarin on prevention of new vascular Background and Purpose-Severe atherosclerosis in the aortic arch is associated with a high risk of recurrent vascular events, but the optimal antithrombotic strategy is unclear. Methods-This prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(81 citation statements)
references
References 46 publications
1
71
0
2
Order By: Relevance
“…14 Aortic arch atheromas greater than 4mm are an indicator of vascular disease, but because treatment with anticoagulation has not been shown to reduce vascular event rates we did not include them on the basis that their presence does not alter management. 15 In contrast we did include spontaneous echo contrast or “smoke” due to its strong association with suspected atrial thromboembolism as a cause of stroke. 21 …”
Section: Discussionmentioning
confidence: 99%
“…14 Aortic arch atheromas greater than 4mm are an indicator of vascular disease, but because treatment with anticoagulation has not been shown to reduce vascular event rates we did not include them on the basis that their presence does not alter management. 15 In contrast we did include spontaneous echo contrast or “smoke” due to its strong association with suspected atrial thromboembolism as a cause of stroke. 21 …”
Section: Discussionmentioning
confidence: 99%
“…32 In clinical practice, aortic atheromas may be an under-recognized cause of stroke because the imaging modalities required to detect them, such as transesophageal echocardiography, are not routinely performed in stroke patients. 33 Early reports suggested a very high rate of stroke recurrence (12% per year) in patients with aortic arch atheromas, 34 but a more recent trial found a much lower rate (<3% per year), 35 suggesting that secular trends in the treatment of atherosclerotic risk factors may be reducing the contribution of aortic atherosclerosis to the burden of stroke.…”
Section: Risk Factors For Cardioembolic Strokementioning
confidence: 99%
“…However, given their manifest atherosclerotic disease, these patients stand to benefit from general recommendations regarding primary prevention of stroke. 122 Data on therapies to prevent recurrent stroke in patients with aortic atherosclerosis 35 will be discussed in a separate section of this Compendium (see section on “Cryptogenic Stroke”).…”
Section: Therapy To Prevent Cardioembolic Strokementioning
confidence: 99%
“… FASTER, The Fast Assessment of Stroke and TIA to prevent Early Recurrence ; CHANCE, Clopidogrel in High‐risk patients with Acute Non‐disabling Cerebrovascular Events ; WASID, Warfarin‐Aspirin Symptomatic Intracranial Disease ; SAMMPRIS, Stenting and Aggressive Medical Management for Preventing Recurrent stroke in Intracranial Stenosis ; CARESS, Clopidogrel and Aspirin for Reduction of Emboli in Symptomatic carotid Stenosis ; CLAIR, CLopidogrel plus Aspirin for Infarction Reduction in acute stroke or transient ischemic attack patients with large artery stenosis and microembolic signals ; ARCH, Aortic Arch Related Cerebral Hazard ; SPAF, Stroke Prevention in Atrial Fibrillation ; ACTIVE, Atrial fibrillation Clopidogrel Trial with Irbesartan for prevention of Vascular Events ; PCI‐CURE, Percutaneous Coronary Intervention‐Clopidogrel in Unstable Angina to Prevent Recurrent Events ; CREDO, Clopidogrel for the Reduction of Events During Observation ; DAPT, 12 or 30 months of Dual Antiplatelet Therapy after Drug‐Eluting Stents ; CUREs, Clopidogrel in Unstable Angina to Prevent Recurrent Events . …”
Section: Resultsmentioning
confidence: 99%
“…There were similar risks of major hemorrhage between both groups. Because of 33 primary outcomes below expectations and long duration of recruitment (8.25 years), this trial lacked statistical power . But in consideration of increasing risks of vascular deaths with well‐conducted warfarin therapy and the complexity of INR‐adjusted dosing, the antiplatelet strategy of DAPT for 90 days and clopidogrel monotherapy for long‐term use may be more advisable in clinical practice.…”
Section: Patients With Noncardioembolic Ischemic Strokementioning
confidence: 99%